Peran Neonatal Comfort Care di Neonatal Intensive Care Unit - Andhika Wicaksana; Rocky Wilar; Johnny L. Rompis (e-CliniC, 2024)
Abstract: Comfort is an important component of the treatment of neonates in the National Intensive Care Unit (NICU). Due to the efforts given in the NICU, neonates tend to be exposed with various surroundings which made them receive excessive stimuli. These can lead to increased level of stress and pain, and have an impact on the health and growth of the neonates in the NICU. Therefore, it is necessary to carry out procedures to keep the baby comfortable by maintaining the stress level through neonatal comfort care. This study aimed to determine the role of neonatal comfort care during the care of neonates in the NICU. This was a literature review study. Literatures were searched in PubMed, Google Scholar, and Clinical Key databases. The results obtained 10 literatures to be reviewed. The statistical results showed that through the implementation of pharmacological and non-pharmacological procedures, neonatal comfort care had a good impact on physiological distress and neonates’ comfort based on the comfort rating scale for neonates in the NICU. In conclusion, neonates’ comfort in the NICU increases significantly after being given neonatal comfort care. Keywords: Neonatal Comfort Care; Neonatal Intensive Care Unit; neonates in care   Abstrak: Menjaga kenyamanan neonatus merupakan komponen penting dalam perawatan di lingkungan Neonatal Intensive Care Unit (NICU). Dalam upaya pengobatan yang dilaksanakan di NICU, neonatus akan terpapar lingkungan yang bervariasi hingga menerima stimuli berlebihan yang dapat menyebabkan peningkatan stres maupun rasa nyeri akibat perawatan invasif yang dilaksanakan. Oleh karena itu diperlukan prosedur pelaksanaan dalam memelihara kenyamanan neonatus untuk menjaga tingkat stres melalui neonatal comfort care. Penelitian ini bertujuan untuk mengetahui peran neonatal comfort care pada perawatan neonatus di NICU melalui suatu literature review. Pencarian literatur dilakukan di database PubMed, Google Scholar, dan Clinical Key. Hasil penelitian mendapatkan 10 literatur untuk diulas. Hasil statistik dari artikel yang diulas menunjukkan bahwa neonatal comfort care melalui pelaksanaan prosedur farmakologi dan non-farmakologi memiliki berdampak baik terhadap distres fisiologis dan kenyamanan neonatus berdasarkan skala penilaian kenyamanan terhadap neonatus yang berada di lingkungan NICU. Simpulan penelitian ini ialah kenyamanan neonatus yang berada di lingkungan NICU meningkat bermakna secara statistik setelah pemberian neonatal comfort care. Kata kunci: Neonatal Comfort Care; Neonatal Intensive Care Unit; bayi dalam perawatan